The secret letters of the monk who sold his ferrari eaudiobook - Sharma, Robin (HighBridge Audio, 2018)
After a bizarre encounter with his lost cousin, Julian Mantle-a former high-powered lawyer who suddenly vanished into the Himalayas-Jonathan Landry is compelled to travel across the planet to retrieve letters and mementos that carry the extraordinary secrets that Julian discovered throughout his life. On a remarkable journey that includes visits to the sensual tango halls of Buenos Aires, the haunting catacombs of Paris, the gleaming towers of Shanghai and the mystical deserts of Sedona, The Secret Letters of The Monk Who Sold His Ferrari reveals astounding insights on reclaiming your personal power, being true to yourself and fearlessly living your dreams.